Relationship between students’ attitudes in space science with their achievements in the field - Abd Majid, Rosadah; Abdullah, Mardina; Bais, Badariah; Bahri, Nor Syaidah; Mokhtar, Mohd Hezri; Bahari, Siti Aminah (Scientific Research Publishing Inc, 2018)
The purpose of this study is to identify the relationship between students’ attitude in space science with their achievement in the field. This study also examines students’ performance in space science. A total of 458 of secondary school students participated in this study. The questionnaire for this study was divided into two parts. The first part contains 9 items about students’ attitudes towards space science while the second part consists of 20 questions of general knowledge about space science. The findings show that students’ general knowledge about space science is at moderate level. The result also shows a significant relationship between students attitude with their achievement towards space science.